A Reflection of Urban Corruption in Batman movie by Matt Reeves through Social Realism Perspective - Radif Muhammad Fathoni; Wisnu Ragil Ananta; Euis Meinawati (Universitas Islam Negeri Palopo, 2026)
This study examines how The Batman (2022) represents urban corruption through a Social Realism perspective. Using a qualitative descriptive method, the research analyzes selected scenes, dialogues, and visual elements that depict political, institutional, and social corruption within Gotham City. The findings indicate that corruption in the film is portrayed as systemic rather than individual, embedded in political authority, law enforcement, and urban structures. Through realist aesthetics and spatial representation, the film reflects contemporary concerns regarding institutional failure and socio-economic inequality. By applying Raymond Williams’ concept of Social Realism, this study demonstrates that a mainstream superhero film can function as a critical reflection of structural corruption in modern urban society. This research contributes to film studies by integrating corruption analysis within a social-realist framework applied to contemporary popular cinema.